The economic impact of pocket parks on residential property values: case study--Madison, Wisconsin - Mwende, Mbaka Mourine (University of Wisconsin--Whitewater, 2018)
When value of a property is assessed, the true determinants of the value of that property is in the attributes attached to that property. What individuals are willing to pay for is the attribute package that will give the maximum utility. Hedonic modelling has been used to appraise the value attached to this attribute. In this study, we use hedonic analysis to determine the value attached to pocket parks when valuing residential property. Our findings show that parks size does have value and it is translated in the value of property. The magnitude of the impact is biggest on parks that are not more than 1.5 acres. For this park sizes, houses near parks that are 0.1 acres bigger value 129 dollars more, above 1.5 acres the magnitude to the impact on house value decreases. Proximity to the park also does increase the value of a house. Also, the further the distance from the house to the nearest park, the lower the value of that house. Therefore, it is important to preserve open spaces even in metropolitan areas for their value on property prices. This increased value equally increases income of home owners and also this benefits the local government because as the home value increase, property tax they receive from these homes go up.
This file was last viewed in Microsoft Edge.
Keywords: Real property--Valuation--Wisconsin--Madison; Parks--Economic aspects--Wisconsin--Madison